STUDY OF ANTIGENOTOXIC POTENTIAL OF THE ROSEHIP (ROSA MAJALIS HERRM.) OF THE FAMILY ROSACEAE - Zhonderbek Zhazyra Aybekkyzy; Kolumbayeva Saule Zhanabayevna; Lovinskaya Anna Vladimirovna; Voronova Nina (Academic Journal of Physical and Chemical Sciences, 2021)
Increasing the body’s resistance to various environmental pollutants’ adverse effects is one of medicine’s essential tasks. In this regard, an active search for antimutagens to eliminate or weaken mutagens’ effect in the body is currently underway. One of the promising sources of antimutagenic compounds is the medicinal plant Rosa majalis Herrm (rosehips). The genotoxic and antigenotoxic activity of rosehips was studied on cells of bone marrow, spleen, liver, and kidneys of laboratory mice using an alkaline variant Comet assay. It was found that rosehip infusions in various concentrations (infusion, diluted infusion and herbal tea) do not have a genotoxic effect on the cells of the studied organs of laboratory animals. The medicinal rosehip’s combined action with classical mutagen MMS significantly reduced (p<0.01) MMS-induced mutagenesis level. The various rosehip infusions used did not show statistically significant differences among themselves. The results obtained indicate the antigenotoxic activity of R. majalis infusions.